Preparation and physical characterization of amorphous silicon semiconductor films - Fernández Chillcce, Enver (1999)
In this work, we present our first results in the elaboration and characterization of thin film amorphous silicon (a-Si: H). The films were obtained by an original reactiv “DC glow discharge” process, which, compared to other results obtained with the same equipment, show now very Good optical quality. This goal allows us the measurement of the optical parameters (n, k) of our probes in a great spectral range. At this report, we show also some complementary results related to the semiconductor behaviour as the electrical conductivity and seebeck effect.